2018
DOI: 10.1371/journal.pone.0209339
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the heterogeneity of labor and delivery units: A quantitative analysis of space and design

Abstract: This study assessed labor and delivery (L&D) unit space and design, and also considered correlations between physical space measurements and clinical outcomes. Design and human factors research has increased standardization in high-hazard industries, but is not fully utilized in medicine. Emergency department and intensive care unit space has been studied, but optimal L&D unit design is undefined. In this prospective, observational study, a multidisciplinary team assessed physical characteristics of ten L&D un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…Overall, our findings support existing evidence that the labor and delivery unit environment varies widely across the U.S. and that differences in design may impact care [ 7 , 8 , 36 , 37 ]. Testing different configurations of ORs and even entire labor and delivery units during actual and simulated obstetric emergencies would allow researchers to measure how design may impact performance and care delivery.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Overall, our findings support existing evidence that the labor and delivery unit environment varies widely across the U.S. and that differences in design may impact care [ 7 , 8 , 36 , 37 ]. Testing different configurations of ORs and even entire labor and delivery units during actual and simulated obstetric emergencies would allow researchers to measure how design may impact performance and care delivery.…”
Section: Discussionsupporting
confidence: 85%
“…Previous research has found significant variation among existing hospitals in labor and delivery OR size and design layout despite similarities in equipment and processes [ 7 , 8 ]. This work suggests emergency Cesarean deliveries are performed in spaces designed based on available guidelines [ 9 – 11 ], building codes [ 12 ], and/or local constraints, but the spaces have not been fully optimized or standardized equivalently to spaces in other high-reliability organizations (e.g., cockpits in aviation, control rooms in nuclear power plants, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Institutional refusal was the only exclusion criteria. 17 The institutional review board at the host institution approved the project protocol on July 13, 2015 and we have renewed every year since. We consented our participants by providing them with a research information sheet, allowing them a chance to read it over and ask questions before we embarked on the site visit.…”
Section: Methodsmentioning
confidence: 99%
“…We also interviewed a convenience sample of on-duty clinicians. While we made formal quantitative measurements, 17 we made the decision to keep our qualitative observations open-ended, unstructured, and observational and therefore did not follow formal interview guides. Because we were touring operational units with patients present, we did not record our interviews to ensure patients' privacy.…”
Section: Ideate (Brainstorm)mentioning
confidence: 99%
“…These physical space requirements can prove inadequate when full maternal and neonatal resuscitation teams assemble in a delivery room. The impact of physical design on maternal clinical outcomes and patient safety is starting to be recognized, but the effect of space constraints on the performance of neonatal resuscitation teams and patient outcomes is yet to be considered [38,39,40]. As a result, the ideal physical design to optimize human performance is unknown at this time.…”
Section: Physical Ergonomic Challengesmentioning
confidence: 99%